Unlocking Potential: OFSP Training Empowers Local Communities in Malawi - Pankuku, J.; Chipungu, F.; Jogo, W.; Munda, E. (2025)
This report documents a capacity-building initiative on orange-fleshed sweetpotato (OFSP) processing and puree utilization conducted in southern Malawi. Targeting women-led small businesses, farmers, and youth, the training strengthened technical, food safety, and entrepreneurial skills for producing OFSP-based bakery products. The initiative demonstrates how value addition and inclusive capacity development can enhance food security, improve nutrition, and generate income opportunities while strengthening local sweetpotato agri-food systems.